Peran Nilai Hedonik Konsumsi dan Reaksi Impulsif sebagai Mediasi Pengaruh Faktor Situasional terhadap Keputusan Pembelian Impulsif di Butik Kota Malang - Rohman, Fatchur (Jurnal Aplikasi Manajemen, 2009)
The objective of this research is to examine in a empirical manner influence of physical surrounding to buying impulsiveness; influence of temporal perspectivers to buying impulsiveness; influence of social surrounding to hedonic consumption value; influence of buying impulsiveness to impulse buying decision; and influence of hedonic consumption value to impulse buying decision. The research samples are 100 people with convenience sampling's method. To test hypotheses, this research uses path analysis. The research result shows that physical surrounding and temporal perspectives affect to the buying impulsiveness; and buying impulsiveness affect to the impulse buying decision, social surrounding, and antecedent states affect to hedonic consumption value, but hedonic consumption value doesn't affect to impulse buying decision. The research result shows that situational factor affect to impulse buying decision through buying impulsiveness.